The Influence of Leadership Style, Motivation, Work Environment, and Work Discipline On Employee Performance at PT. Central Bank Asia (BCA) Rantauprapat - Evelyn, Evelyn; Harahap, Nova Jayanti; Halim, Abd. (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This type of research is quantitative, the place of this research is PT. Bank Central Asia (BCA) Rantauprapat. The population in this study was 37 employees of PT. Bank Central Asia (BCA) Rantauprapat. Due to the number of employees of PT. Bank Central Asia (BCA) Rantauprapat has 37 people, so all employees of PT. Bank Central Asia (BCA) Rantauprapat was taken as the object of research. The data collection techniques used in the research were observation, documentation, and questionnaires using a Likert scale. This research uses classical assumption tests which include the data normality test, heteroscedasticity test, and multicollinearity test. Multiple linear regression analysis was tested using partial (t), simultaneous (F), and coefficient of determination tests. The research results stated that leadership style, motivation, work environment, and work discipline simultaneously had a positive and significant effect on employee performance at PT. Bank Central Asia (BCA) Rantauprapat. The R Square value from the coefficient of determination analysis is 0.900, meaning that employee performance can be explained by the variables leadership style, motivation, work environment, and work discipline by 90%, while the rest can be explained by other variables not examined in this research.